Twelfth night, or, What you will - Nunn, Trevor; Bonham Carter, Helena, 1966-; Grant, Richard E., 1957-; Hawthorne, Nigel; Kingsley, Ben, 1943-; Smith, Mel, 1952-2013; Staunton, Imelda, 1956-; Stephens, Toby, 1969-; Stubbs, Imogen, 1961-; Shakespeare, William, 1564-1616
Shipwrecked on an unfriendly Illyrian shore, Viola, believing her twin brother is dead, disguises herself in male attire and joins the retinue of the lovesick Duke Orsino.